DEIKSIS DALAM NASKAH DRAMA GERR KARYA I PUTU WIJAYA DAN IMPLIKASINYA DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH MENENGAH PERTAMA (SMP) - ni made mulyasari; mulyanto widodo; edi suyanto (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2013)
Deixis plays important roll in script of drama for its function as the indicator of another undetermined thing or function. Therefore, how the context is in the script of drama Gerr by I Putu Wijaya become the problem of this study. The method of this study is qualitative descriptive. The source of data is in form of the script of drama Gerr by I Putu Wijaya in 69 pages. The data of this study is the dialog which includes deixis.Based on the data analysis, the data found are in form of deixis of person, deixis of space, and deixis of time. They are different from deixis of endophora which consist of anaphora and cataphora. Deixis of person is divided to three person; first, second and third person. All these three deixis are found in this study of script of drama, so as the deixis of time and space. Deixis of anaphora is also found in this study. According to its intensity, the entire study of the script of drama Gerr I Putu Wijaya, the dialog found consist of 219 deixis; 138 deixis of person, 36 deixis of time and 45 deixis of space. Based on those deixis, it’s known that the deixis much found according to the data analysis is the deixis of persona. This investigation of deixis implicates to the learning process of Indonesian language. This study can be used as the learning resources, especially writing.Key Word  : deiksis pesona, time deiksis, room deiksis, katafora, drama, and implication